Pattern of Injuries Inflicted in Cases of Child Abuse in a Tertiary Care Centre in Central India — A Retrospective Study - Ingale, Sundeep; Jiwane, Ashok; Mohite, Prakash (Journal of Neonatal Surgery, 2025)
Background: Child abuse remains a critical public health issue worldwide, including in India. Understanding injury patterns aids early diagnosis and intervention. Objectives: To study the pattern, anatomical location, and duration of injuries in confirmed cases of child abuse at a tertiary care centre in Central India. Methods: A retrospective analysis was conducted over 5 years (January 2018–December 2022) on 164 confirmed cases. Variables such as age, gender, injury type, anatomical site, and duration were recorded. Statistical analysis was performed using Chi-square test; p<0.05 was considered significant. Results: Among 164 cases, 98 (59.8%) were males and 66 (40.2%) were females. Most victims (47.6%) were aged 6–12 years. Bruises (43.9%) were the most common injury. Head and neck (37.2%) were the most frequently involved anatomical site. Acute injuries (<7 days old) predominated (69.5%). Statistically significant differences were observed in fracture patterns (p=0.014) and burns (p=0.038) between genders. Conclusion: Bruises and fractures are predominant in child abuse cases, mainly involving the head and neck regions. Early identification based on injury patterns can enhance child protection